Experimental and numerical investigations of the geometry influence on gas accumulation using a V-shaped forest model. (September 2016) - Coudour, Bruno; Chetehouna, Khaled; Conan, Boris; Aubrun, Sandrine; Kaiss, Ahmed; Garo, Jean-Pierre
Abstract: Accumulation of gas inside a valley exposed to crosswind is experimented in this paper to extrapolate it to a case of a forest fire approaching a thalweg. Experimentations were done inside a wind tunnel using a 1/400 forest model configured as a valley with two different internal angles. The forest was modelled by mesh cylinders so that a parallel is possible with a real forest thanks to similitude laws. Gas emission was ensured by 400 tubes introduced inside the cylinders and supplied with ethane which acted as a tracer. The 400 tubes were divided into four independent parts of 100 tubes, inside and outside the valley, to be able to study independently the influence of the different zones of the forest model on the gas accumulation. We focused on the measurements of velocity by Laser-Doppler Velocimetry (LDV) and concentration with a Flame Ionization Detector (FID) to visualise the flow and quantify the accumulation of ethane. Analysing velocity, turbulence and concentration, a stagnation point was observed in the thalweg for the flattest valley and a recirculation zone for the deepest one where gas accumulation reached up to four times the concentration measured outside the valley due to airflow. The study of the influence of the different emission zones showed that gas accumulation mainly comes from the zones inside the valley. All these data permitted us to validate a numerical modelling which will enable us to study more cases, varying above all gas density but also choosing more valley angles and configurations. Another interest of the numerical model is the possibility of adding a thermal model. Highlights: Recirculation zone is observed for the lowest internal angle of V-shape valley model. Maximal concentration is located in the thalweg for α = 80° and above lee side for 50°. For 80°, concentration inside the thalweg is twice the one measured above flat forest. For 50°, concentration above lee side is 3.5 times the one measured above flat forest. A numerical model has been validated against experimental data for further study.